Кримінологічна характеристика та профілактика злочинів у сфері зовнішньоекономічної діяльності - Білецький, Василь Олексійович; Белецкий, Василий Алексеевич; Biletsky, Vasyl О. (My University, 1999)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.08 — кримінальне право і кримінологія; кримінально-виконавче право. — Одеська державна юридична акаде- мія, Одеса, 1999. В роботі розглянуто комплекс теоретичних та практичних питань з проблем боротьби зі злочинністю у сфері зовнішньоекономічної діяльності, зокрема, особлива увага приділяється розробці організаційно-правових заходів, спрямованих на попередження злочинів у зовнішньоекономічній сфері та усунення умов, які їм сприяють.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.08 — уголовное право и криминология; уголовно-исполнительное право. — Одесская государственная юридическая академия, Одесса, 1999. В работе рассмотрен комплекс теоретических и практических вопросов, связанных с проблемами борьбы с преступностью в сфере внешнеэкономической деятельности, в частности, особое внимание уделяется разработке организационно-правовых мер, направленных на предотвращение преступлений во внешнеэкономической сфере и устранение способствующих им условий.

Candidate thesis, speciality 12.00.08 — criminal law and criminology; criminal executive law. Odessa state Academy of law, Odessa, 1999. The following thesis aims at disclosing actual problems of external economic activity crime. The work gives a complex analysis of criminological aspects of the causes and conditions composing the grounds, and genesis of external economic activity crime, proposes and recommends improvements to the system of state command on enterprises engaged in the external economic activity, and depicts the ways to raise the standards of legal and other command and control boards responsible for warning and preventive measures against such kind of offence. The document also reveals the dynamics of external economic activity crimes for the period of 1995-1998, made on the basis of the Ministry of internal affairs, State Tax Inspection, and state Customs Inspection analysis and statistic materials. The most specific crime did in the sphere of external economic activity are paid the major attention to and are very thoroughly depicted in this research. Some cases have got professional criminological characteristics and structural analysis adjacent to this or that sort of grime did. The thesis give grounds for necessary changes and amendments to the existing legislation, describe the characteristics of certain crime species, connected with customs law breach, foreign currency legislation, offshore deposits of money and valuables, fake business activity conduct. The research vividly discloses drawbacks of the current legislative articles regulating creation and state registration of new companies proposes ways and Methods of the legislation alterations to absolutely exclude the penetration of people with criminal record into newly arranged enterprises. The Idea is also to addend the legislation articles with the power delegated to fax and internal affairs boards to check and control origination of funds forming the basis of particular enterprise to be commended. There has a conclusion been made, that absence of such a legal mechanism enabled black money turn legal economy and criminals integrate within state boards, forming so called organised delinquency. The articles of this work clearly state the connectivity between the external activity crime and such negative phenomena as funds outflow and growth of the external debt of Ukraine, concentration of considerable amounts of funds on the some particular bank accounts belonging to Ukrainians abroad. The analysis of police and tax inspection units activity made it possible to determine the ways of tobacco and alcohol smuggling and develop major remedies to struggle it and on international level also. The positions considered in the thesis research make criminological characteristics of external activity crime more detailed, which contributes into measures and approaches to such crimes, neutralisation along with conditions causing them.
Білецький В. О. Кримінологічна характеристика та профілактика зло- чинів у сфері зовнішньоекономічної діяльності : автореф. дис. ... канд. юрид. наук : 12.00.08 / В. О. Білецький; кер. роботи В. О. Глушков; Нац. ун.-т "Одеська юридична академія". – Одеса, 1999. – 19 с.
Keywords: злочинність у зовнішньоекономічній сфері; попередження злочинів; криміногенні фактори; діяльність правоохоронних органів; преступность во внешнеэкономической сфере; предупреждение преступлений; криминогенные факторы; деятельность правоохранительных органов; criminality; external economic activity; preventing crimes; factors of criminality; law enforcement agencies activity